Agriculture in Poland and the Protection of the Natural Environment. Results of Expert Studies - Arkadiusz PIWOWAR (Communications of International Proceedings, 2020)
Agricultural activity has a considerable impact on shaping of the natural environment. It is directly associated with the consumption of natural resources and changes in the spatial development, and hence it becomes necessary to take into account environmental issues in the agricultural economics in the macroscale, mesoscale and microscale (in agricultural policy, analyses of economic effectiveness in agriculture in specific spatial ranges, ethical dimension of the economic activity, social responsibility of farmers, etc.). The article presents the opinions of experts regarding the causes of problems related to the threat to the natural environment in rural areas in Poland and the proposed remedial measures. The survey was conducted at the turn of 2017/2018 and concerned current problems in the studied subject area. The main objective of the research was to identify the reasons why farmers did not take actions aimed at protection of the environment, as well as to indicate the measures (at the central and local levels) that could improve this situation. The experts indicated many possible actions that may contribute to an improvement of the condition of the natural environment in rural areas in Poland.
Keywords: Rural Areas; Agriculture; Environmental; Protection; Tag Cloud